Cultivation of Dioscorea alata L. and Dioscorea aculeata L. in Universiti Putra Malaysia Bintulu Sarawak Campus - Mohd Amiru Norul Din. (2010.)
A study was carried out about cultivation of Diocorea alata L. (white and purple) and Diocorea aculeata L. in Share Farm 1 in Universiti Putra Malaysia Bintulu Sarawak Campus. A total of 36 white D. alata, 43 purple D. alata tuber pieces and 50m whole tubers D. aculeata were planted. White D. alata leaves are simple and alternate shaped with muctonate apex and unifoliolate venation. The young leaf is sagittate and small acute at the apex. Stem produce from new shoots will twin in right when climb. Purple D. alata leaves are lanceolate shaped with acuminate or caudate apex and unifoliolate venation. The young leaf is red colour and sagittage shaped. Stem produce through new shoot in red colour and twin right on staking. Red colour on stem and leave will change in 3-4 days. Dioscorea aculeata leaves are simple and cordate with mucronate apex, unifoliolate venation. The young leaf was deltoid shape and brown in colour. Stem twin left and have thorn. Germination rate of tubers white D. alata, purple D. alata and D. aculeata were 97.22%, 90.70% and 74.00% respectively. Growing stages were categories into four stages: (1) emergence of first shoot, (2) a vein develop, (3) trailing vein and climbing development stage and (4) end season. The duration for all stages of white D. alata, purple D. alata and D aculeata were approximately 220 days, 230 days and 250 days respectively. Fresh weight tuber per plant after harvest is 0-2.2 kg. White D. alata was produce single tuber and purple D. alata was produce single or more tubers but unshaped in both. Tuber surface is brown or black colour. Dioscorea aculaeta is rounded or unshaped tuber with brown colour.
Project paper (B.S.Bi.) - Universiti Putra Malaysia Kampus Bintulu Sarawak, 2010.